2009
DOI: 10.1177/1090198109339993
|View full text |Cite
|
Sign up to set email alerts
|

In the Dark: Young Men’s Stories of Sexual Initiation in the Absence of Relevant Sexual Health Information

Abstract: A growing body of research is investigating the effectiveness of abstinence only sexual education. There remains a dearth of research on the relevant sexual health information available to young men who have sex with men (YMSM). Drawing on a mixed-methods study with 526 YMSM, this study explores how and where YMSM receive relevant information on sexual health/behavior. Findings indicate that information related to gay men’s sexuality is not readily available from family, friends or schools. At initiation of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
142
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(152 citation statements)
references
References 37 publications
7
142
0
3
Order By: Relevance
“…PrEP awareness, or lack thereof, among participants is representative of an underdeveloped sexuality education system to serve MSM and other sexual minorities in relatively rural states (Kubicek, Beyer, Weiss, Iverson, & Kipke, 2010;Poon & Saewyc, 2009). This supports previous research that has advocated for sexual health information that is inclusive of discussion of PrEP in combination with other behavioral strategies to be shared among the MSM population by providers, social service agencies, and their peers (Oldenburg et al, 2014;Taylor et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…PrEP awareness, or lack thereof, among participants is representative of an underdeveloped sexuality education system to serve MSM and other sexual minorities in relatively rural states (Kubicek, Beyer, Weiss, Iverson, & Kipke, 2010;Poon & Saewyc, 2009). This supports previous research that has advocated for sexual health information that is inclusive of discussion of PrEP in combination with other behavioral strategies to be shared among the MSM population by providers, social service agencies, and their peers (Oldenburg et al, 2014;Taylor et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the family, a number of studies have documented difficulties in communication about sex and relationships between parents and children (for example, Coffelt, 2017;Hyde, Carney, Drennan, Butler, Lohan, & Howlett, 2010). Where parents are heterosexual, heteronormativity is likely to be a key feature of conversations (Kubicek et al, 2010;Martin, 2009). Likewise, Kubicek et al (2010) qualitative interviews with young MSM revealed that whilst peers were an important source of information about sex, during adolescence, this mostly focused on heterosexual sex.…”
Section: Discussionmentioning
confidence: 99%
“…Where parents are heterosexual, heteronormativity is likely to be a key feature of conversations (Kubicek et al, 2010;Martin, 2009). Likewise, Kubicek et al (2010) qualitative interviews with young MSM revealed that whilst peers were an important source of information about sex, during adolescence, this mostly focused on heterosexual sex. This therefore could act as an additional barrier for young people wishing to know about same-sex sexual relationships, because their peers may be unwilling and/or unable to discuss this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, viewing SEM may aid in the learning of performing same-sex sex 20,21 ; promote self-recognition of same-sex attractions 20,22 ; and clarify sexual self-labels 23 . However, SEM depicting male same-sex acts often contain several potentially risky sexual behaviors known to be associated with STI risk, including UAI, ejaculation in the mouth (EM), and ejaculation in/on or rubbed into the anus (EA) 24 .…”
Section: Sem Consumption and Sexual Risk Behaviors Among Msmmentioning
confidence: 99%